ЭФФЕКТ ПОГЛОЩЕНИЯ СВЕТА НА ЭЛЕКТРОФИЗИЧЕСКИЕ ХАРАКТЕРИСТИКИ СОЛНЕЧНЫХ ЭЛЕМЕНТОВ - Комилов, Аслиддин; Насруллаев, Юсуф (Innovatsion texnologiyalar, 2022)
Light absorption on the parameters of solar cells with the ZnO structure: Al/i-ZnO / CdS/CuIn1-xGax (S, Se) 2 / Mo after reverse bias. Analysis of the experimental data showed that the effect of light absorption is opposite to the effect of reverse bias and can almost completely compensate for it over time. At the same time, the recovery of the open circuit voltage in a solar cell with a normal buffer layer thickness requires more time than in a solar cell with a thin buffer layer.